WITH THE RUSSIAN EMPIRE OF THE FERGANA REGION AT THE BEGINNING OF THE 20TH CENTURY ECONOMIC RELATIONS (Scientific journal of the Fergana State University, 2025)
The article reflects on the economic relations of the Fergana region with the Russian Empire at the beginning of the 20th century on the basis of local archival materials and other historical sources, and consequently on the transformation of the region into the Russian market of industrial goods, as well as the penetration of Russian capital into the region.